Warm winters are associated to more intense West Nile virus circulation in southern Spain - Sergio Magallanes; Francisco Llorente; María José Ruiz-López; Josué Martínez-de la Puente; Martina Ferraguti; Rafael Gutiérrez-López; Ramón Soriguer; Pilar Aguilera-Sepúlveda; Raúl Fernández-Delgado; Miguel Ángel Jímenez-Clavero; Jordi Figuerola (Emerging Microbes and Infections)
West Nile virus (WNV) is the most widely distributed mosquito-borne flavivirus in the world. This flavivirus can infect humans causing in some cases a fatal neurological disease and birds are the main reservoir hosts. WNV is endemic in Spain, and human cases have been reported since 2004. Although different studies analyse how climatic conditions can affect the dynamics of WNV infection, very few use long-term datasets. Between 2003 and 2020 a total of 2,724 serum samples from 1,707 common coots (Fulica atra) were analysed for the presence of WNV-specific antibodies. Mean (SD) annual seroprevalence was 24.67% (0.28) but showed high year-to-year variations ranging from 5.06% (0.17) to 68.89% (0.29). Significant positive correlations (p < 0.01) were observed between seroprevalence and maximum winter temperature and mean spring temperature. The unprecedented WNV outbreak in humans in the south of Spain in 2020 was preceded by a prolonged period of escalating WNV local circulation. Given current global and local climatic trends, WNV circulation is expected to increase in the next decades. This underscores the necessity of implementing One Health approaches to reduce the risk of future WNV outbreaks in humans. Our results suggest that higher winter and spring temperatures may be used as an early warning signal of more intense WNV circulation among wildlife in Spain, and consequently highlight the need of more intense vector control and surveillance in human inhabited areas.